FUNDAMENTALS OF COMPUTER MATHEMATICAL MODELING (Scientific journal of the Fergana State University, 2024)
The article is a study of scientific and methodological research solutions for computer mathematical modeling and their practical application using AnyLogic software. Also, AnyLogic equipment, which is used to create computer mathematical modeling, is based on their capabilities. The computer mathematical model created in the AnyLogic environment is presented visually.